(untitled) (Semiárida, 2018)
The barley cropping area has been increased in La Pampa Province during the last four years. An infection caused by Ramularia collo-cygni, a fungus that induces leaf necrotic spotting in barley, is presently spreading across the Pampean Region as an emerging disease. The goal of the present work was to carry out the diagnosis of this disease and initial exploration of its distribution in La Pampa Province. Phytopathological analyses were performed on barley samples collected from the northern and southern areas of the province. As results of this work, symptoms and signs of the disease are described and illustrated in this article, as well as features of the pathogen development in different culture media, giving way to the first report relating Ramularia leaf spot of barley for La Pampa. DOI: http://dx.doi.org/10.19137/semiarida.2016(01).29-33